Placental extracellular vesicles express active dipeptidyl peptidase IV; levels are increased in gestational diabetes mellitus - Neva Kandzija (Journal of Extracellular Vesicles, 2019)
Gestational diabetes mellitus (GDM) is the most common metabolic disorder in pregnancy and is characterized by insulin resistance and decreased circulating glucagon-like peptide-1 (GLP-1). GDM resolves rapidly after delivery implicating the placenta in the disease. This study examines the biological functions that cause this pathology. The placenta releases syncytiotrophoblast-derived extracellular vesicles (STB-EVs) into the maternal circulation, which is enhanced in GDM. Dipeptidyl peptidase IV (DPPIV) is known to play a role in type 2 diabetes by breaking down GLP-1, which in turn regulates glucose-dependent insulin secretion. STB-EVs from control and GDM women were analysed. We show that normal human placenta releases DPPIV-positive STB-EVs and that they are higher in uterine than paired peripheral blood, confirming placental origin. DPPIV-bound STB-EVs from normal perfused placentae are dose dependently inhibited with vildagliptin. DPPIV-bound STB-EVs from perfused placentae are able to breakdown GLP-1 in vitro. STB-EVs from GDM perfused placentae show greater DPPIV activity. Importantly, DPPIV-bound STB-EVs increase eightfold in the circulation of women with GDM. This is the first report of STB-EVs carrying a biologically active molecule that has the potential to regulate maternal insulin secretion.